A Genetic Screen for Maternal-Effect Suppressors of decapentaplegic Identifies the eukaryotic translation initiation factor 4A in Drosophila - Li, Jinghong (Copyright © 2005 by the Genetics Society of America, 2005)
The Dpp signaling pathway is essential for many developmental processes in Drosophila and its activity is tightly regulated. To identify additional regulators of Dpp signaling, we conducted a genetic screen for maternal-effect suppressors of dpp haplo-insufficiency. We screened ∼7000 EMS-mutagenized genomes and isolated and mapped seven independent dominant suppressors of dpp, Su(dpp), which were recovered as second-site mutations that resulted in viable flies in trans-heterozygous with dpp(H46), a dpp null allele. Most of the Su(dpp) mutants exhibited increased cell numbers of the amnioserosa, a cell type specified by the Dpp pathway, suggesting that these mutations may augment Dpp signaling activity. Here we report the unexpected identification of one of the Su(dpp) mutations as an allele of the eukaryotic translation initiation factor 4A (eIF4A). We show that Su(dpp)(YE9) maps to eIF4A and that this allele is associated with a substitution, arginine 321 to histidine, at a well-conserved amino acid and behaves genetically as a dominant-negative mutation. This result provides an intriguing link between a component of the translation machinery and Dpp signaling.